Heterojunction nanoring electrocatalyst and preparation method and application thereof

CN117512646BActive Publication Date: 2026-10-30SUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311505925.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2026-10-30
Estimated Expiration
2043-11-13

AI Technical Summary

Technical Problem

因此,该类材料的进一步大规模工业化应用始终受到阻碍

Benefits of technology

[0037]1.本发明提供了一种对于电解水析氢反应的催化活性远超商业Pt/C电催化剂的异质结纳米环电催化剂。由金属有机框架材料衍生而来的氮掺杂石墨烯网具有高导电率、高比表面积和丰富的微介孔孔隙,有效提升电子传递能力,增强传质能力,充分暴露活性位点,并促进析氢反应中的反应中间体和生成的气体产物的转移,具有更高的反应动力学,而且还可以作为碳基底稳固的锚定Pt基金属间化合物-氮化物异质结纳米环。更为重要的是,Pt基金属间化合物与金属氮化物的异质结构的构建使得该催化剂具备高催化活性、长时间抗腐蚀性和高稳定性,且Pt基金属间化合物-氮化物异质结纳米环状结构在有效提升活性位点利用率的同时还可以有效阻止催化剂在反应过程中的结构破坏和活性衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117512646B_ABST
    Figure CN117512646B_ABST
Patent Text Reader

Abstract

The application discloses a kind of heterojunction nanoring electrocatalyst and its preparation method and application, the heterojunction nanoring electrocatalyst is the porous graphene net loaded with platinum-based intermetallic compound-nitride, the metal is VB group and / or VIB group transition metal, the mass fraction of the platinum-based intermetallic compound is 10-20%, and the mass fraction of nitride is 5-10%.The preparation method of the application adopts metal organic framework derived carbon template strategy, and the Pt-based intermetallic compound-nitride heterojunction of nanoring structure is firmly anchored on the porous graphene net, and the preparation process is simple, the raw material is cheap and convenient to source, environment-friendly, and highly reproducible.The heterojunction nanoring electrocatalyst provided by the application can exhibit excellent hydrogen evolution catalytic activity and durability under large current density, which is beneficial to larger-scale commercial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterials technology, specifically to a heterojunction nanoring electrocatalyst, its preparation method, and its application. Background Technology

[0002] Faced with the demands of a green energy transition and severe environmental pollution, there is an urgent need to develop green, efficient, and sustainable clean energy sources to replace traditional fossil fuel systems. Among these, hydrogen (H2), as an environmentally friendly high-energy-density energy carrier, has gradually attracted widespread attention from researchers. Of the various hydrogen production methods, water electrolysis is considered a highly promising sustainable approach due to its advantages such as simple operation, no harmful greenhouse gas emissions during the process, and flexible coupling with renewable energy sources (such as wind or solar power). Electrocatalytic water splitting involves the cathode hydrogen evolution reaction (HER) and the anodic oxygen evolution reaction (OER). For the HER reaction, platinum (Pt) is currently the best-performing known catalyst; however, it still faces challenges such as high cost, slow kinetics, and poor stability, which significantly limit its large-scale commercial application. Therefore, reducing the amount of Pt and introducing inexpensive transition metals to develop inexpensive, highly active, and durable HER catalysts has become a research focus in both academia and industry.

[0003] Pt-based intermetallic compounds, composed of noble metal Pt and transition metals (M), are promising electrocatalytic alloys for HER (hermetic catalysis) (Adv. Mater. 2023, 35, 2302067). Benefiting from strong d-orbital interactions and ordered stoichiometry, intermetallic compounds not only exhibit optimized electronic structure and improved catalytic efficiency but also achieve enthalpy stability, significantly enhancing catalyst stability. However, individual intermetallic compounds are prone to aggregation due to strong cohesive energy, resulting in insufficient utilization of active sites and requiring further release of catalytic activity.

[0004] Meanwhile, transition metal nitrides (TMNs) are ideal candidate materials for the decomposition of pure water or seawater due to their high conductivity and strong corrosion resistance. However, the Gibbs free energy (ΔG) of hydrogen atoms adsorbed at the active sites of TMNs is a concern. H* The HER catalytic performance of most previously reported TMN-based electrocatalysts is inferior to that of Pt (ChemCatChem, 2020, 12, 2962-296). However, due to the high conductivity and strong corrosion resistance of these TMNs, they can be combined with Pt-based intermetallic compounds to achieve a comprehensive improvement in catalytic activity and durability. However, the rational construction of metal nitrides and Pt-based intermetallic compounds still presents significant challenges.

[0005] Furthermore, regarding the issue of metal-based catalyst agglomeration, combining metal-based materials with carbon-based materials is generally considered an effective solution. This not only effectively promotes the dispersion of the metal-based material and exposes its active sites, but also significantly enhances the catalyst's corrosion resistance in strong acid / alkaline electrolytes and improves catalytic stability due to the introduction of carbon materials (Adv. Mater. 2023, 35, 2303). Currently developed carbon-based supports include porous carbon, graphene, and carbon nanotubes. However, the carbon / metal composite catalysts developed so far still suffer from relatively poor proton transport capabilities, such as slow transfer of reaction intermediates and insufficient escape of the gaseous product H2. When these materials are used as catalysts under conditions requiring high current densities for industrial water electrolysis to produce hydrogen, their hydrogen evolution catalytic activity is often unsatisfactory. Therefore, the further large-scale industrial application of these materials remains a significant obstacle. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a heterojunction nanoring electrocatalyst, its preparation method, and its application. The heterojunction nanoring electrocatalyst is a porous graphene network supported on a platinum-based intermetallic compound—nitride. The preparation method is simple, uses inexpensive and readily available raw materials, is environmentally friendly, and has high reproducibility. The obtained electrocatalyst exhibits excellent hydrogen evolution catalytic activity at high current densities, which is beneficial for large-scale commercial applications.

[0007] This invention is achieved through the following technical solution:

[0008] The first aspect of the present invention provides a heterojunction nanoring electrocatalyst, wherein the heterojunction nanoring electrocatalyst is a porous graphene network supported on a platinum-based intermetallic compound-nitride, wherein the metal is a group VB and / or group VIB transition metal, the mass fraction of the platinum-based intermetallic compound is 10-20%, and the mass fraction of the nitride is 5-10%.

[0009] This invention uses nitrogen-doped porous graphene mesh as a substrate. On one hand, its high specific surface area and nitrogen doping effectively suppress the accumulation of Pt-based intermetallic compound-nitride heterojunctions, promoting their uniform dispersion. Simultaneously, the dual-solvent adsorption and carbothermal reduction methods enable strong coupling between the carbon matrix and the nanorings, firmly anchoring the Pt-based intermetallic compound-nitride heterojunction. Furthermore, the porous nature of the graphene mesh promotes proton transport during catalyst operation, significantly enhancing its catalytic activity. On the other hand, the unique nanoring structure of the Pt-based intermetallic compound-nitride heterojunction effectively exposes active sites and exhibits excellent structural stability during operation. The presence of metal nitrides in the heterostructure further enhances the catalyst's conductivity and corrosion resistance, modulates the electronic structure of the Pt-based intermetallic compound, and further lowers the energy barrier for the HER reaction. These outstanding advantages enable this catalyst to exhibit superior performance in the electrocatalytic hydrogen evolution reaction.

[0010] Furthermore, the transition metal is one or more of W, Mo, and V.

[0011] A second aspect of this invention provides a method for preparing the heterojunction nanoring electrocatalyst described in the first aspect, comprising the following steps:

[0012] S1: Zinc-based metal-organic framework material is mixed with a stripping agent, heated in an inert gas environment, and acid-washed to remove zinc impurities to obtain nitrogen-doped porous graphene mesh.

[0013] S2: The nitrogen-doped porous graphene network is dispersed in an organic solvent to obtain a dispersion. Platinum salt solution and transition metal salt solution are added to the dispersion. After drying, the dispersion is heated in an inert gas environment to obtain the heterojunction nanoring electrocatalyst.

[0014] This invention employs a metal-organic framework-derived carbon template strategy to stably anchor a nanoring-structured Pt-based intermetallic compound-nitride heterojunction onto an ultrathin porous graphene mesh. A molten salt-assisted thermal exfoliation method is used to derive the Pt-based metal-organic framework material into a nitrogen-doped porous graphene mesh. Using this material as a substrate, metal salts containing Pt and transition metals are adsorbed onto the nitrogen-doped porous graphene mesh via a dual-solvent adsorption method. A porous graphene mesh-supported Pt-based intermetallic compound-nitride heterojunction nanoring electrocatalyst is then prepared through high-temperature thermal reduction.

[0015] The preparation method provided by this invention is simple, uses inexpensive and readily available raw materials, is environmentally friendly, and highly reproducible. It produces a large number of porous graphene mesh-supported platinum-based intermetallic compound-nitride heterojunction nanorings. This method can be extended to synthesize multi-component Pt-based intermetallic compounds and multi-component metal nitride heterojunctions supported by porous graphene mesh; or composites of porous graphene mesh with adjustable thickness and porosity supported by porous graphene mesh and multi-component Pt-based intermetallic compounds and multi-component metal nitride heterojunctions, demonstrating considerable universality and scalability.

[0016] Further, in step S1, the zinc-based metal-organic framework material is prepared by mixing an aqueous solution of zinc nitrate hexahydrate and dimethylimidazole, stirring and reacting, separating the precipitate and drying it to obtain the zinc-based metal-organic framework material.

[0017] Furthermore, the molar ratio of zinc nitrate hexahydrate to dimethylimidazole is 1:(8-10).

[0018] Further, in step S1, the amount of zinc-based metal-organic framework material added is 200-500 mg.

[0019] Further, in step S1, the stripping agent is potassium chloride and lithium chloride, and the mass ratio of potassium chloride to lithium chloride is (4-10):1.

[0020] Furthermore, in step S1, the amount of the stripping agent added is 3-5g.

[0021] Further, in step S1, the pickling is performed using dilute acid, which is dilute hydrochloric acid or dilute sulfuric acid with a concentration of 0.5–2 M.

[0022] Furthermore, in step S1, the temperature of the heat treatment is 900–1000°C, and the time is 2–4 hours.

[0023] Furthermore, in step S2, the concentration of nitrogen-doped porous graphene mesh in the dispersion is 5–15 mg / mL.

[0024] Further, in step S2, the concentration of the platinum salt solution is 0.2 to 0.3 M, and the concentration of the transition metal salt is set according to the different element types of the platinum-based intermetallic compound, with reference to the concentration of the platinum salt.

[0025] Furthermore, in step S2, the platinum salt is preferably H2PtCl6, and the transition metal salt is preferably anhydrous chloride.

[0026] Furthermore, in step S2, the heating treatment temperature is 900–1000°C, and the time is 2–4 hours.

[0027] Specifically, the preparation method of the heterojunction nanoring electrocatalyst includes the following steps:

[0028] S1: After mixing an aqueous solution of zinc nitrate hexahydrate and dimethylimidazole and stirring for 30-40 min, the mixture was allowed to stand for 4-5 h. The precipitate was separated and dried to obtain the zinc-based metal-organic framework material. The zinc-based metal-organic framework material was thoroughly mixed and ground with a stripping agent and placed in a tube furnace under an inert atmosphere for heat treatment. It was then soaked in deionized water multiple times and acid-washed to remove salt and zinc impurities. After washing with deionized water again, it was dried to obtain a nitrogen-doped porous graphene mesh.

[0029] S2: The nitrogen-doped porous graphene network is dispersed in an organic solvent to obtain a dispersion. A DMF solution containing platinum salt and transition metal salt is added to the dispersion. The supernatant is removed, and the bottom precipitate is dried and placed in a tube furnace under an inert atmosphere for heating treatment to obtain the heterojunction nanoring electrocatalyst.

[0030] A third aspect of the present invention provides a three-electrode electrolytic cell, comprising a working electrode, a counter electrode, a reference electrode, and an electrolyte, wherein the heterojunction nanoring electrocatalyst described in the first aspect is deposited on the working electrode.

[0031] Further, the method for depositing the heterojunction nanoring electrocatalyst on the working electrode is as follows: dispersing the heterojunction nanoring electrocatalyst in ethanol containing a perfluorosulfonic acid polymer (Nafion) to obtain a dispersion, and dropping the dispersion onto the working electrode until the loading mass reaches 0.8–1 mg·cm³. -2 .

[0032] Furthermore, the working electrode is a glassy carbon electrode, the counter electrode is a carbon rod, and the reference electrode is an Hg / HgO electrode.

[0033] Furthermore, the electrolyte is a KOH solution saturated with hydrogen gas.

[0034] The fourth aspect of this invention provides the application of the heterojunction nanoring electrocatalyst described in the first aspect or the three-electrode electrolyzer described in the third aspect in the electrolysis of water.

[0035] The electrocatalyst obtained by this invention exhibits excellent hydrogen evolution catalytic activity and durability at high current densities, which is beneficial for large-scale commercial applications.

[0036] The beneficial effects of this invention are:

[0037] 1. This invention provides a heterojunction nanoring electrocatalyst with catalytic activity far exceeding that of commercial Pt / C electrocatalysts for the hydrogen evolution reaction in water electrolysis. The nitrogen-doped graphene network, derived from metal-organic framework materials, possesses high conductivity, high specific surface area, and abundant micro- and mesoporous pores, effectively enhancing electron transport and mass transfer capabilities, fully exposing active sites, and promoting the transfer of reaction intermediates and gaseous products in the hydrogen evolution reaction, resulting in higher reaction kinetics. Furthermore, it can serve as a stable anchor for Pt-based intermetallic compound-nitride heterojunction nanorings on a carbon substrate. More importantly, the heterostructure of the Pt-based intermetallic compound and metal nitride gives the catalyst high catalytic activity, long-term corrosion resistance, and high stability. Moreover, the Pt-based intermetallic compound-nitride heterojunction nanoring structure effectively improves the utilization rate of active sites while effectively preventing structural damage and activity decay of the catalyst during the reaction process.

[0038] 2. The preparation method provided by this invention is simple, uses inexpensive and readily available raw materials, is environmentally friendly, and has high reproducibility. This method can be extended to synthesize heterojunctions of multi-component Pt-based intermetallic compounds and multi-component metal nitrides supported by porous graphene networks; or composites of porous graphene networks with adjustable thickness and porosity supported by porous graphene networks, multi-component Pt-based intermetallic compounds, and multi-component metal nitride heterojunctions, demonstrating considerable universality and scalability.

[0039] 3. The heterojunction nanoring electrocatalyst obtained in this invention exhibits excellent hydrogen evolution catalytic activity and durability at high current densities, which is beneficial for large-scale commercial applications. In a 1M KOH electrolyte, the overpotential of this catalyst during the hydrogen evolution reaction is η. 10mA·cm-2 =28mV and η 500mA·cm-2 =370mV, and can be maintained at 10mA·cm -2 The high current density can reach 26 hours without degradation. Attached Figure Description

[0040] Figure 1 The X-ray powder diffraction pattern of the Pt2W-WN@PGM electrocatalyst of Example 1 of this invention is shown.

[0041] Figure 2 This is a transmission electron microscope (TEM) image of the Pt2W-WN@PGM electrocatalyst from Example 1 of the present invention.

[0042] Figure 3 This is a transmission electron microscope (TEM) image of the Pt3Sn@PGM electrocatalyst of Comparative Example 1 of the present invention.

[0043] Figure 4The HER linear sweep voltammetry curves are for Pt2W-WN@PGM in Example 1 of the present invention, Pt3Sn@PGM in Comparative Example 1, and 20wt% Pt / C electrocatalyst.

[0044] Figure 5 The HER current density-time curve of the Pt2W-WN@PGM electrocatalyst in Example 1 of this invention is shown. Detailed Implementation

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0046] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0047] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.

[0048] Example 1

[0049] A heterojunction nanoring electrocatalyst, wherein the heterojunction nanoring electrocatalyst is a porous graphene network (Pt2W-WN@PGM) supported on Pt2W intermetallic compound-nitride, wherein the mass fraction of Pt2W is 10% and the mass fraction of WN is 5%, and the preparation method includes the following steps:

[0050] S1: Dissolve 0.89g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 1.64g di-methylimidazole in 40mL of deionized water respectively, mix the solutions, stir for 30min, let stand for 4h, separate the white precipitate and dry to obtain the zinc-based metal-organic framework material; mix 300mg of zinc-based metal-organic framework material with 8g KCl and 1g LiCl and grind thoroughly, put it into a tube furnace under nitrogen atmosphere and heat at 900℃ for 4h, soak in deionized water several times to remove salt, wash away residual zinc impurities with 1M dilute hydrochloric acid, wash again with deionized water and dry to obtain nitrogen-doped porous graphene mesh;

[0051] S2: 40 mg of nitrogen-doped porous graphene mesh was dispersed in 4 mL of positive ethanol and ultrasonically dispersed to obtain a dispersion. 0.2 mL of DMF solution containing 0.265 M H2PtCl6·(H2O)6 and 0.2 M WCl6 was added to the above dispersion and ultrasonic dispersion was continued for 1 hour. The supernatant was removed, and the bottom precipitate was dried and placed in a tube furnace under a nitrogen atmosphere for heating at 1000 °C for 2 hours to obtain the heterojunction nanoring electrocatalyst (Pt2W-WN@PGM).

[0052] Figure 1 The image shows the X-ray powder diffraction (XRD) pattern of the heterojunction nanoring electrocatalyst (Pt2W-WN@PGM). As can be seen from the figure, the derived peaks of Pt2W-WN@PGM are mainly attributed to Pt2W and WN, while a broad peak belonging to carbon is also shown at around 26 degrees, proving the successful synthesis of the Pt2W intermetallic compound-tungsten nitride heterojunction nanoring composite supported on a porous graphene network.

[0053] Figure 2 This is a transmission electron microscope (TEM) image of a heterojunction nanoring electrocatalyst (Pt2W-WN@PGM). Figure 2 The TEM images (a) to (c) show that the Pt2W-WN@PGM material exhibits a structure of uniformly loaded nanorings on a two-dimensional ultrathin graphene network, with the diameter of the nanorings ranging from 50 to 100 nm. Figure 2 The high-magnification transmission electron microscopy (HRTEM) image of d clearly shows lattice fringes of 0.19 nm and 0.23 nm, which correspond to the (101) plane of WN and the (101) plane of Pt2W, respectively, proving the formation of the heterostructure of Pt2W and WN.

[0054] Example 2

[0055] A heterojunction nanoring electrocatalyst, wherein the heterojunction nanoring electrocatalyst is a porous graphene network (Pt3Mo-MoN@PGM) supported on Pt3Mo intermetallic compound-nitride, wherein the mass fraction of Pt3Mo is 10% and the mass fraction of MoN is 5%, and the preparation method includes the following steps:

[0056] S1: Dissolve 0.89g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 1.64g di-methylimidazole in 40mL of deionized water respectively, mix the solutions, stir for 30min, let stand for 4h, separate the white precipitate and dry to obtain the zinc-based metal-organic framework material; mix 300mg of zinc-based metal-organic framework material with 8g KCl and 1g LiCl and grind thoroughly, put it into a tube furnace under nitrogen atmosphere and heat at 900℃ for 4h, soak in deionized water several times to remove salt, wash away residual zinc impurities with 1M dilute hydrochloric acid, wash again with deionized water and dry to obtain nitrogen-doped porous graphene mesh;

[0057] S2: 40 mg of nitrogen-doped porous graphene mesh was dispersed in 4 mL of positive ethanol and ultrasonically dispersed to obtain a dispersion. 0.2 mL of DMF solution containing 0.265 M H2PtCl6·(H2O)6 and 0.15 M MoCl5 was added to the dispersion and ultrasonic dispersion was continued for 1 hour. The supernatant was removed, and the bottom precipitate was dried and placed in a tube furnace under a nitrogen atmosphere for heating at 1000 °C for 2 hours to obtain the heterojunction nanoring electrocatalyst (Pt3Mo-MoN@PGM).

[0058] Example 3

[0059] A heterojunction nanoring electrocatalyst, wherein the heterojunction nanoring electrocatalyst is a porous graphene network (Pt3V-VN@PGM) supported on Pt3V intermetallic compound-nitride, wherein the mass fraction of Pt3V is 10% and the mass fraction of VN is 5%, and the preparation method includes the following steps:

[0060] S1: Dissolve 0.89g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 1.64g di-methylimidazole in 40mL of deionized water respectively, mix the solutions, stir for 30min, let stand for 4h, separate the white precipitate and dry to obtain the zinc-based metal-organic framework material; mix 300mg of zinc-based metal-organic framework material with 8g KCl and 1g LiCl and grind thoroughly, put it into a tube furnace under nitrogen atmosphere and heat at 900℃ for 4h, soak in deionized water several times to remove salt, wash away residual zinc impurities with 1M dilute hydrochloric acid, wash again with deionized water and dry to obtain nitrogen-doped porous graphene mesh;

[0061] S2: 40 mg of nitrogen-doped porous graphene mesh was dispersed in 4 mL of positive ethanol and ultrasonically dispersed to obtain a dispersion. 0.2 mL of DMF solution containing 0.265 M H2PtCl6·(H2O)6 and 0.15 M VCl6 was added to the dispersion and ultrasonic dispersion was continued for 1 hour. The supernatant was removed, and the bottom precipitate was dried and placed in a tube furnace under a nitrogen atmosphere for heating at 1000 °C for 2 hours to obtain the heterojunction nanoring electrocatalyst (Pt3V-VN@PGM).

[0062] Example 4

[0063] A heterojunction nanoring electrocatalyst, wherein the heterojunction nanoring electrocatalyst is supported on Pt2W 0.5 Mo 0.5 Porous graphene networks of intermetallic compounds-nitrides (Pt2W) 0.5 Mo 0.5 -W 0.5 Mo 0.5 N@PGM), the Pt2W 0.5 Mo 0.5 The mass fraction is 10%, W 0.5 Mo 0.5 The mass fraction of N is 5%, and the preparation method includes the following steps:

[0064] S1: Dissolve 0.89g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 1.64g di-methylimidazole in 40mL of deionized water respectively, mix the solutions, stir for 30min, let stand for 4h, separate the white precipitate and dry to obtain the zinc-based metal-organic framework material; mix 300mg of zinc-based metal-organic framework material with 8g KCl and 1g LiCl and grind thoroughly, put it into a tube furnace under nitrogen atmosphere and heat at 900℃ for 4h, soak in deionized water several times to remove salt, wash away residual zinc impurities with 1M dilute hydrochloric acid, wash again with deionized water and dry to obtain nitrogen-doped porous graphene mesh;

[0065] S2: 40 mg of nitrogen-doped porous graphene mesh was dispersed in 4 mL of positive ethanol and ultrasonically dispersed to obtain a uniform dispersion. 0.2 mL of a DMF solution containing 0.265 M H₂PtCl₆·(H₂O)₆, 0.1 M WCl₆, and 0.1 M MoCl₆ was added to the dispersion, and ultrasonic dispersion was continued for 1 hour. The supernatant was removed, and the bottom precipitate was dried and placed in a tube furnace under a nitrogen atmosphere for heating at 1000 °C for 2 hours to obtain the heterojunction nanoring electrocatalyst (Pt₂WCl₆·(H₂O)₆). 0.5 Mo 0.5 -W 0.5 Mo 0.5 N@PGM).

[0066] Example 5

[0067] A heterojunction nanoring electrocatalyst, wherein the heterojunction nanoring electrocatalyst is a supported Pt2W 1 / 3 Mo 1 / 3 V 1 / 3 Porous graphene networks of intermetallic compounds-nitrides (Pt2W) 1 / 3 Mo 1 / 3 V 1 / 3 -W 1 / 3 Mo 1 / 3 V 1 / 3 N@PGM), the Pt2W 1 / 3Mo 1 / 3 V 1 / 3 The mass fraction is 10%, W 1 / 3 Mo 1 / 3 V 1 / 3 The mass fraction of N is 5%, and the preparation method includes the following steps:

[0068] S1: Dissolve 0.89g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 1.64g di-methylimidazole in 40mL of deionized water respectively, mix the solutions, stir for 30min, let stand for 4h, separate the white precipitate and dry to obtain the zinc-based metal-organic framework material; mix 300mg of zinc-based metal-organic framework material with 8g KCl and 1g LiCl and grind thoroughly, put it into a tube furnace under nitrogen atmosphere and heat at 900℃ for 4h, soak in deionized water several times to remove salt, wash away residual zinc impurities with 1M dilute hydrochloric acid, wash again with deionized water and dry to obtain nitrogen-doped porous graphene mesh;

[0069] S2: 40 mg of nitrogen-doped porous graphene mesh was dispersed in 4 mL of normal ethanol and ultrasonically dispersed to obtain a uniform dispersion. 0.2 mL of a DMF solution containing 0.265 M H₂PtCl₆·(H₂O)₆, 0.065 M WCl₆, 0.065 M MoCl₆, and 0.065 M VCl₃ was added to the dispersion, and ultrasonic dispersion was continued for 1 hour. The supernatant was removed, and the bottom precipitate was dried and placed in a tube furnace under a nitrogen atmosphere for heating at 1000 °C for 2 hours to obtain the heterojunction nanoring electrocatalyst (Pt₂W₃). 1 / 3 Mo 1 / 3V 1 / 3 -W 1 / 3 Mo 1 / 3 V 1 / 3 N@PGM).

[0070] Comparative Example 1

[0071] A porous graphene mesh supported Pt3Sn intermetallic compound electrocatalyst (Pt3Sn@PGM) is prepared by the following steps:

[0072] S1: Dissolve 0.89g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 1.64g di-methylimidazole in 40mL of deionized water respectively, mix the solutions, stir for 30min, let stand for 4h, separate the white precipitate and dry to obtain the zinc-based metal-organic framework material; mix 300mg of zinc-based metal-organic framework material with 8g KCl and 1g LiCl and grind thoroughly, put it into a tube furnace under nitrogen atmosphere and heat at 900℃ for 4h, soak in deionized water several times to remove salt, wash away residual zinc impurities with 1M dilute hydrochloric acid, wash again with deionized water and dry to obtain nitrogen-doped porous graphene mesh;

[0073] S2: 40 mg of nitrogen-doped porous graphene mesh was dispersed in 4 mL of positive ethanol and ultrasonically dispersed to obtain a uniform dispersion. 0.2 mL of DMF solution containing 0.265 M H2PtCl6·(H2O)6 and 0.1 M SnCl2·2H2O was added to the dispersion and ultrasonic dispersion was continued for 1 hour. The supernatant was removed, and the bottom precipitate was dried and placed in a tube furnace under a nitrogen atmosphere for heating at 1000 °C for 2 hours to obtain a porous graphene mesh-supported Pt3Sn intermetallic compound electrocatalyst (Pt3Sn@PGM).

[0074] Figure 3 The image shows a transmission electron microscope (TEM) image of a porous graphene network-supported Pt3Sn intermetallic compound electrocatalyst (Pt3Sn@PGM). As can be seen from the image, the Pt3Sn@PGM material exhibits a structure in which nanoparticles are uniformly loaded onto a two-dimensional graphene network. The diameter of the nanoparticles is about 100 nm, and they do not form a nanoring structure.

[0075] Test Example 1

[0076] The electrocatalytic HER performance of the Pt2W-WN@PGM electrocatalyst of Example 1, the Pt3Sn@PGM electrocatalyst of Comparative Example 1, and the commercial 20wt% Pt / C electrocatalyst was tested using the following methods:

[0077] Using an Hg / HgO electrode as the reference electrode and a carbon rod as the counter electrode, the electrocatalyst was deposited on a glassy carbon electrode as the working electrode. Linear scan voltammetry was performed at a scan rate of 5 mV / s in a 1M KOH solution saturated with hydrogen as the electrolyte.

[0078] The specific steps for depositing the electrocatalyst onto the glassy carbon electrode are as follows: 5 mg of the electrocatalyst is dispersed in a mixture of 970 μL of ethanol and 30 μL of Nafion, and after ultrasonication until uniform dispersion, the slurry is dropped onto the glassy carbon electrode until the loaded mass reaches 0.85 mg·cm³. -2 .

[0079] Test results are as follows Figure 4 As shown, Figure 4 The figures show the HER linear sweep voltammetry curves of Pt2W-WN@PGM in Example 1, Pt3Sn@PGM in Comparative Example 1, and the 20wt% Pt / C electrocatalyst. As can be seen from the figures, the Pt2W-WN@PGM electrocatalyst achieves a 10 mA·cm⁻¹ voltammetry result. -2 The current density requires only 28mV overpotential; while reaching 500mA·cm -2 The high current density requires only 370mV overpotential, which is far superior to the HER performance of Pt3Sn@PGM material and commercial 20wt% Pt / C catalyst.

[0080] Test Example 2

[0081] The electrocatalytic HER performance of the Pt2W-WN@PGM electrocatalyst in Example 1 was tested. The test method was as follows: the Pt2W-WN@PGM electrocatalyst was loaded with 10 mA·cm⁻¹. -2 The current density of HER in 1M KOH electrolyte.

[0082] Test results are as follows Figure 5 As shown, Figure 5 This is the HER current density-time curve of the Pt2W-WN@PGM electrocatalyst in Example 1 of the present invention. As can be seen from the figure, the Pt2W-WN@PGM electrocatalyst maintains a current density of 10 mA·cm⁻¹. -2 The current density remained stable for 26 hours without decay, demonstrating excellent hydrogen evolution catalytic stability and durability.

[0083] When the electrocatalysts prepared in Examples 2-5 were used for the electrochemical hydrogen evolution reaction, the results were comparable to those in Example 1.

[0084] In this invention, Pt-based intermetallic compound-nitride heterojunction nanorings are supported on a porous graphene network. This not only enhances electron and proton transport capabilities but also promotes the uniform dispersion of the Pt-based intermetallic compound-nitride heterojunction nanorings, increasing the exposure of active sites. Furthermore, the Pt-based intermetallic compound-nitride heterojunction nanoring structure achieves both full utilization of active sites and a significant improvement in intrinsic catalytic activity and durability. Therefore, this electrocatalyst exhibits excellent electrocatalytic activity and durability in the hydrogen evolution reaction under high current.

[0085] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A heterojunction nanoring electrocatalyst, characterized in that, The heterojunction nanoring electrocatalyst is a porous graphene network supported on a platinum-based intermetallic compound-nitride, wherein the metal is a group VB and / or group VIB transition metal, the mass fraction of the platinum-based intermetallic compound is 10-20%, and the mass fraction of the nitride is 5-10%; the transition metal is one or more of W, Mo, and V. The preparation method of the heterojunction nanoring electrocatalyst includes the following steps: S1: Zinc-based metal-organic framework material is mixed with a stripping agent, heated in an inert gas environment, and acid-washed to remove zinc impurities to obtain nitrogen-doped porous graphene mesh. S2: The nitrogen-doped porous graphene network is dispersed in an organic solvent to obtain a dispersion. Platinum salt solution and transition metal salt solution are added to the dispersion. After drying, the dispersion is heated in an inert gas environment to obtain the heterojunction nanoring electrocatalyst. In step S2, the heating treatment temperature is 900~1000 ℃ and the time is 2~4 h.

2. The heterojunction nanoring electrocatalyst according to claim 1, characterized in that, In step S1, the zinc-based metal-organic framework material is prepared by mixing an aqueous solution of zinc nitrate hexahydrate and dimethylimidazole, stirring and reacting, separating the precipitate and drying it to obtain the zinc-based metal-organic framework material.

3. The heterojunction nanoring electrocatalyst according to claim 2, characterized in that, The molar ratio of zinc nitrate hexahydrate to dimethylimidazole is 1:(8~10).

4. The heterojunction nanoring electrocatalyst according to claim 1, characterized in that, In step S1, the stripping agent is potassium chloride and lithium chloride, and the mass ratio of potassium chloride to lithium chloride is (4~10):

1.

5. The heterojunction nanoring electrocatalyst according to claim 1, characterized in that, In step S2, the concentration of nitrogen-doped porous graphene mesh in the dispersion is 5~15 mg / mL.

6. The heterojunction nanoring electrocatalyst according to claim 1, characterized in that, In step S2, the concentration of the platinum salt solution is 0.2~0.3 M.

7. A three-electrode electrolytic cell, comprising a working electrode, a counter electrode, a reference electrode, and an electrolyte, characterized in that, The working electrode is deposited with the heterojunction nanoring electrocatalyst according to any one of claims 1-6.

8. The application of the heterojunction nanoring electrocatalyst according to any one of claims 1-6 or the three-electrode electrolyzer according to claim 7 in the electrolysis of water.

Citation Information

Patent Citations

  • Microporous Zn-NC carbon carrier supported PtZnM multi-component alloy catalyst as well as preparation method and application thereof

    CN115881992A